The influence of grit on life satisfaction of Brazilian undergraduate students: academic adaptation as a mediator - Noronha, Ana Paula Porto; Dias-Viana, João Lucas; Cavallaro, Ana Paula Ozório (Frontiers in Psychology, 2024)
Introduction In recent years, research in educational contexts has pointed to the role of grit as a variable related to various positive outcomes, including life satisfaction. Academic adaptation seems vital for the success of academic life in college students. Considering university as an important life context for people pursuing higher education, what is the mediating effect of academic adaptation? This study proposed a mediation model to examine the mediating effect of academic adaptation in the relationship grit and life satisfaction. Methods A sample of 413 undergraduate Brazilian students, age ranging from 18 to 71 years (M = 27.30; SD = 10.20). A correlation analysis was performed between the variables and the following mediation model was tested: Grit (independent variable), academic adaptation (mediating variables) and life satisfaction (dependent variables). Results Mediation analysis indicated that academic adaptation mediated around 46.80% for the factor of consistency of interests and 40.90% of the relationship with perseverance of effort. Thus, the greater the grit of the university student, the greater the grit, which leads to better satisfaction with life. Discussion In recent years, research in educational contexts has pointed to the role of grit as a variable related to various positive outcomes. The findings elucidated that grit in academic context could benefit students’ adaptation process, and the university’s responsibility to improve its students’ softskills, not only for the future stage after university, but also during the student’s schooling.